The Emissions Gap Report 2014 - United Nations Environment Programme (United Nations, 2014)
The UN Environment Emissions Gap Report assesses the latest scientific studies on current and estimated future greenhouse gas emissions and compares these with the emission levels permissible for the world to progress on a least-cost pathway to achieve the goals of the Paris Agreement. This difference between “where we are likely to be and where we need to be” is known as the ‘emissions gap’. The report explores some of the most important options available for countries to bridge the gap.